2002
DOI: 10.1124/jpet.102.037002
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Pharmacodynamic Studies of a Human Serum Albumin-Interferon-α Fusion Protein in Cynomolgus Monkeys

Abstract: Interferon-␣ (IFN-␣) is indicated for the treatment of certain viral infections including hepatitis B and C, and cancers such as melanoma. The short circulating half-life of unmodified IFN-␣ makes frequent dosing (daily or three times weekly) over an extended period (6 -12 months or more) necessary. To improve the pharmacokinetics of IFN-␣ and decrease dosing frequency, IFN-␣ was fused to human serum albumin producing a new protein, Albuferon. In vitro comparisons of Albuferon and IFN-␣ showed similar antivira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(116 citation statements)
references
References 28 publications
7
108
1
Order By: Relevance
“…Plasma half-lives for therapeutic proteins invariably increase with the size of the animal (Mordenti et al, 1991). Allometric scaling from our rat data, in light of experience with other albumin fusion proteins (Osborn et al, 2002), is compatible with a several-day half-life of Albu-CocH in humans, allowing infrequent dosing. Gene transfer represents an alternative mode of delivery that, if perfected, could provide continuous supply.…”
Section: Intervention In Relapse or Reinstatement Of Drugseeking Behasupporting
confidence: 59%
“…Plasma half-lives for therapeutic proteins invariably increase with the size of the animal (Mordenti et al, 1991). Allometric scaling from our rat data, in light of experience with other albumin fusion proteins (Osborn et al, 2002), is compatible with a several-day half-life of Albu-CocH in humans, allowing infrequent dosing. Gene transfer represents an alternative mode of delivery that, if perfected, could provide continuous supply.…”
Section: Intervention In Relapse or Reinstatement Of Drugseeking Behasupporting
confidence: 59%
“…It was shown in vitro, that alb-IFN has the same anti-viral properties as IFN-a, and the induction of ISG is very similar to that of pegIFN-a2a and 2b (Liu et al, 2007). In vivo studies in cynomolgus monkeys revealed a prolonged halflife of alb-IFN in comparison with IFN-a (Osborn et al, 2002). The efficacy of alb-IFN was evaluated in clinical phase IIb studies with IFN-naive patients chronically infected with HCV, in which it was administered every 2 or 4 weeks (Zeuzem et al, 2008).…”
Section: New Ifnsmentioning
confidence: 91%
“…16 Compared to their native proteins, the lower binding affinity and biological potency (about 10 percent or less) in vitro assay had shown in most HSA fusion product. [23][24][25] It was surmised that the increase in molecular size after small parent molecules fused with albumin possibly reduced the numbers of receptors occupied, HSA maybe influenced the binding of receptor but could not affect signal transduction.…”
Section: Discussionmentioning
confidence: 99%